A comparison of local anaesthetics for venepuncture. Issue 4 (1st April 2000) - Arrowsmith, J; Campbell, C
Abstract : AIM: To compare the effectiveness of EMLA cream and Ametop gel in providing analgesia for venous cannulation. METHODS: Single blind study in 120 children. RESULTS: Both anaesthetic agents produced adequate analgesia. However, Ametop gel was more effective, with a statistically significant difference in the pain scores of the two groups (p < 0.05).